Estimate the Prevalence of Depression in Type 2 Diabetes Patients - Zahraa Mohammed AL-Khaqani; Thanaa Shams Al-Deen Al-Turaihi (مجلة الكوفة الطبية)
Background: Diabetes is a chronic disease characterized by high blood sugar levels, resulting from insulin resistance and the destruction of pancreatic beta cells. This disease is associated with several serious complications that are sometimes life-threatening to patients. One of these complications is that it can depression accompanies patients with type 2 diabetes, as it is a Major Depressive Disorder (MDD), and the most important symptoms are social isolation, sleep disturbances, lack of appetite, loss of desire, and passion for daily activities. Opinions differed about the origin of the emergence of this psychological disorder in terms of the involvement of multiple factors, including internal, and some of them are external to causing this disorder. In this study, we will shed light on one of the complications associated with diabetes, which is depression. Method and Results: This cross-sectional study included the selection of 128 individuals diagnosed with type 2 diabetes from the Diabetes and Endocrinology Center located in Najaf, Iraq from August 2023 to October 2023. The study included 43 men and 85 women. The ages of the participants ranged from 30 to 75 years. Patients were randomly selected during their visit to the center. Results: 31(24.2%) individuals did not manifest any symptoms of depression 75.78% suffered from depression, most of the depressed people were women, and the difference between the sexes was statistically significant p-value (0. 002). Conclusion; Our study highlights a striking connection between type 2 diabetes and depression, with a significantly higher incidence of depression in diabetic patients. Additionally, the fact that females are more likely to suffer from depression compared to males also calls for further research into other factors that could potentially exacerbate mental health issues in type 2 diabetes women.